2014
DOI: 10.1111/1469-0691.12501
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-based identification, genotyping and EUCAST antifungal susceptibilities of Trichosporon clinical isolates from Greece

Abstract: Trichosporon yeasts constitute emerging pathogens, implicated in organ-specific and systemic infections. In this first, comprehensive study of Trichosporon clinical isolates in Greece, 42 isolates were identified by sequencing the hypervariable D1/D2 domain of the Large Subunit (LSU) rDNA gene, while Trichosporon asahii were genotyped by sequencing the Intergenic Spacer 1 region, and antifungal susceptibilities were determined by the EDef 7.2 (EUCAST) method, in parallel with the CLSI standard. Trichosporon as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
6
25
1
Order By: Relevance
“…Consistent with previous studies (25,26,29,(31)(32)(33)(34), high AMB MICs were observed for our collection of T. asahii isolates. These in vitro data concur with published AMB therapy failures (34)(35)(36).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies (25,26,29,(31)(32)(33)(34), high AMB MICs were observed for our collection of T. asahii isolates. These in vitro data concur with published AMB therapy failures (34)(35)(36).…”
Section: Discussionsupporting
confidence: 92%
“…The distributions of the T. asahii genotypes varied among different regions. Genotype 1 predominated in our study in China, which is similar to the prevalences in Spain (24), Mexico (25), Brazil (7), Turkey (26), and Japan (3), while genotypes 1 and 3 occur in Argentina (27), Taiwan (28), Thailand (29), and India (30) and genotypes 3 and 4 occur in Greece (31). Interestingly, our results found that genotype 3 strains exhibited higher AMB MICs (Ն2 g/ml) than did genotype 1 strains (P ϭ 0.009).…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, while individual studies did not find any correlation between genotype and in vitro susceptibility, when merging the data available from 4 well-designed studies (Rodriguez-Tudela et al, 2007 ; Guo et al, 2011 ; Yang et al, 2013 ; Arabatzis et al, 2014 ), we noted that genotype 3 strains may exhibit higher MICs to voriconazole than genotype 1 strains: MIC GM 0.12 vs. 0.49 mg/L, p = 0.04, whereas the MIC values of AMB (MIC GM 1.9 vs. 1.2, p = 0.2) and fluconazole (MIC GM 5.2 vs. 5.6, p = 0.7) were similar for both genotypes.…”
Section: Resultsmentioning
confidence: 98%
“…Details from 19 studies having tested at least 10 Trichosporon clinical isolates for a given species with a microdilution method are presented in Tables 3 – 8 (Arikan and Hasçelik, 2002 ; Paphitou et al, 2002 ; Ramos et al, 2004 ; Metin et al, 2005 ; Rodriguez-Tudela et al, 2005 ; de Oliveira Silva et al, 2008 ; Chagas-Neto et al, 2009 ; Taj-Aldeen et al, 2009 ; Thompson et al, 2009 ; Lemes et al, 2010 ; Mekha et al, 2010 ; Guo et al, 2011 ; Sun et al, 2012 ; Tsai et al, 2012 ; Hazirolan et al, 2013 ; Yang et al, 2013 ; Arabatzis et al, 2014 ; Taverna et al, 2014 ; Montoya et al, 2015 ). Up to now, there is no recommendation from the two main consortia (EUCAST and CLSI) regarding the AST of Trichosporon .…”
Section: Resultsmentioning
confidence: 99%
“…However, from 2010 onward the first sporadic cases of Trichosporon spp . resistant to voriconazole were reported [ 9 , 10 ], and a recent study from Greece reported that 38 % of Trichosporon isolates had a MIC ≥ 2 mg/L for voriconazole [ 11 ]. Most of these strains were susceptible to at least one other triazole, and treatment failures were not described in this study.…”
Section: Discussionmentioning
confidence: 99%